Identifikasi pengaruh perceived organizational support terhadap kepuasan kerja dengan work engagement sebagai variabel pemediasi - Sarianti, Rini; Fitria, Yuki; Nazara, Etha Visari (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2018)
The purpose of this research is to analyze (1) the influence of perceived organizational support on job satisfaction (2) the influence of perceived organizational support on employee engagement (3) the influence of perceived organizational support on job satisfaction with employee engagement as a mediating variable. The population in this research are the employees of Department of PT. West Sumatera Regional Development Bank of Padang consist of 115 employees. The samples were selected using Clustered Proportional Random Sampling which the total of the samples are 89 employees. The data used are primary data and secondary data. The data was analyzed using multiple regression analysis with mediating variable. The result of this research shows (1) perceived organizational support has a positive and significant relationship on job satisfaction (2) perceived organizational support has a positive and significant relationship on employee engagement (3) employee engagement become a mediator on the effect of perceived organizational support on job satisfaction.Keywords: Perceived organizational support; job satisfaction; employee engagement.